Pengembangan Media Audio Visual Berbasis Powerpoint untuk Meningkatkan Kemampuan Menghafal Kosakata Bahasa Inggris di Sekolah Dasar - Kholisoh, Nur; Rahmawati, Emma; Al-Aidrus, Firza M.; Fauziah, Giska Enny (SITTAH: Journal of Primary Education, 2024)
This article discusses the results of a study aimed at developing PowerPoint-based audiovisual media as a learning strategy to improve vocabulary memorization skills in English language learning. The researchers developed engaging and practical PowerPoint-based audiovisual media using a Research & Development (R&D) approach with the ADDIE model. Data were collected through observations, interviews, questionnaires, and documentation. The evaluation results from media design experts, English language experts, and learning experts indicated that the developed learning media fell into the highly suitable category with a percentage above 80%. Subsequently, the media was tested with small and large groups. Furthermore, the hypothesis testing using paired t-test showed that the PowerPoint-based audiovisual media on the topic of the human body was effective in improving students' vocabulary memorization skills in English language learning, with a calculated t-value of 2.845 > tabulated t-value of 2.028. Based on all these findings, it can be concluded that the use of PowerPoint-based audiovisual media has a significant impact on students' vocabulary memorization skills.